Accountability through (Inter)Action? A Framework of Affordances for Understanding Civil Society Accountability on Social Media Platforms - Cecilia Gullberg; Nils Gustafsson (Social Media + Society)
This article investigates how social media can enable and constrain civil society organizations’ (CSOs) discharge of accountability. Based on a comparative analysis of the Instagram, Facebook, and Twitter (X) posts of the Swedish Red Cross during 1 year ( N  = 1014), we propose a framework of affordances that illustrate how platform features, practices, norms, and perceptions about audiences jointly shape the accountability potential of a platform. Accountability is overall more content- than process-oriented, emphasizing visibility of action rather than far-reaching social interactivity. Our study, however, reveals important differences between Instagram and Facebook, on the one hand, and Twitter, on the other. Whereas accountability is more short-term, scripted, and donor-oriented in the former, it is more abstract and ad hoc, with mainly indirect efforts at interactivity, in the latter. Our framework of affordances sheds light on the hitherto under-researched intersection between the literature on CSO accountability and the literature on CSO use of social media.